Myth (De)Constructed: Some Reflections Provoked by Dan Wylie’s Book Myth of Iron: Shaka in History - Leśniewski, Michał (My University, 2011)
The aim of this article is to discuss perspectives on and interpretations of South African history in the early 19th century: in this case, an early history of the Zulu state and a biography of Shaka. Firstly it is an overview of Dan Wylie book, Myth of Iron: Shaka in History. This book, which is a very important voice in the discussion of the beginnings of the Zulu State, is a pretext to look at contemporary so-called revisionist historiography. Far from being averse to revisionist attitudes, it is useful to observe the method behind revisionist criticism as presented in this book – how it criticises earlier historiography and primary sources, and how it elaborates new interpretation. This leads to another dimension of this text: a reflection on the creation and deconstruction of historical stereotypes. Dan Wylie’s book is an example of how deconstruction of one set of myths and stereotypes may lead to introduction of another set. Even in agreeing with the view that history is just a constructed story of the past, it is also important to take note of the means by which this story is created.
Keywords: African studies; South Africa; historiography; 18th and 19th century; Zulu state in history; Shaka in history; interpretations of history and historical processes